2002
DOI: 10.1080/09553000210151639
|View full text |Cite
|
Sign up to set email alerts
|

Life span, cancer and non-cancer diseases in mouse exposed to a continuous very low dose of γ-irradiation.

Abstract: Continuous 10 cGy year(-1) gamma-irradiation had no adverse effect on malignant or non-malignant diseases in this strain of mouse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…In a previous study, we have shown that HS incidence in C57BL/6J female mice was reduced by administration of chronic lowdose irradiation (4). During this study, we obtained 41 cases of HS in nontreated mice, for which we were aware of unexpected associated hematopoietic disorders.…”
Section: Introductionmentioning
confidence: 89%
“…In a previous study, we have shown that HS incidence in C57BL/6J female mice was reduced by administration of chronic lowdose irradiation (4). During this study, we obtained 41 cases of HS in nontreated mice, for which we were aware of unexpected associated hematopoietic disorders.…”
Section: Introductionmentioning
confidence: 89%
“…For several years, we have perfected a unique model of chronic irradiation to γ-rays able to deliver a continuous low-dose rate irradiation of 10cGy/year. Life-long irradiation of C57Bl/6J female mice was responsible for a delay of death by lymphoma ( Courtade et al . 2002 ) although it had no effect on life span.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, fractionated low dose radiation over a period of several weeks has been shown to increase the number of T-regulatory cells (Tago et al 2008; Tsukimoto et al 2008). Radiation-induced up-regulation of antiinflammatory immune cells has been associated with a lower frequency of lymphomas (Courtade et al 2002; Ina et al 2005; Lacoste-Collin et al 2007; Mitchel 2007; Nakatsukasa et al 2008; Tago et al 2008; Tsukimoto et al 2008; Tsuruga et al 2007). In contrast, however, a higher frequency of hematological malignancies and chromosome aberrations has been reported in mice and dogs after continuous low dose-rate irradiation (Seed et al 2002a, 2002b; Tanaka et al 2007, 2008, 2009).…”
mentioning
confidence: 99%